2008
DOI: 10.5194/aab-51-531-2008
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between fore and hind hoof dimensions in the horse (<i>Equus caballus</i>)

Abstract: Abstract. The aim of the study was to define differences between front and hind hooves in dimensions and proportions of the measurements in horses of various breeds. 77 mares four to thirteen years old of four breeds belonging to different origin types were evaluated: Purebred Arabian horses, halfbred Anglo-Arabian horses, primitive Polish Konik horses and Polish Cold-Blooded horses. The dimensions were measured after trimming. Means in particular groups and differences between fore and hind hooves were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Wall thickness of both breeds was similar to values for this parameter found by Stachurska et al . ( 26 ) and Tocci et al . ( 30 ).…”
Section: Discussionmentioning
confidence: 96%
“…Wall thickness of both breeds was similar to values for this parameter found by Stachurska et al . ( 26 ) and Tocci et al . ( 30 ).…”
Section: Discussionmentioning
confidence: 96%
“…A significantly greater percentage of hoof conformation faults and disorders was detected in the front legs as compared with the hind legs, which may be a result of uneven strain on legs due to their different functions and biomechanics of movement. Due to the locations of the center of gravity of the horse and of the head and neck, and the absorption of shocks caused by landing and hitting the ground with a greater vertical velocity, the front legs are subject to more concussion than the hind legs (14)(15)(16)(17)(18). The greater and differently directed forces to which a front leg hoof is exposed in comparison with hind legs not only determine differences in hoof and sole shape (2,18), but can also make horses more prone to developing certain disorders in their front hooves.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the locations of the center of gravity of the horse and of the head and neck, and the absorption of shocks caused by landing and hitting the ground with a greater vertical velocity, the front legs are subject to more concussion than the hind legs (14)(15)(16)(17)(18). The greater and differently directed forces to which a front leg hoof is exposed in comparison with hind legs not only determine differences in hoof and sole shape (2,18), but can also make horses more prone to developing certain disorders in their front hooves. Leise et al (19) and Wylie et al (20) reported that laminitis was associated more often with front than hind hooves.…”
Section: Discussionmentioning
confidence: 99%
“…In this space color, all colors are defined in the H channel. With this, it is only necessary to select the color by the H channel and the saturation and brightness by the S and V channels [29].…”
Section: B Carbon Fiber Horse Shoementioning
confidence: 99%
“…Therefore, in parallel to the collection of FBG signals, videos of the horse moving were recorded with fuzzy logic recognizing colors in the captured images. This identification allows a visual analysis of the mechanical deformation exercised by the animal during it's gait, identifying every member of the horse and inserting colors based on the FBGs signals [29]. This technique can be used in rapid identification of possible health problems.…”
Section: Introductionmentioning
confidence: 99%